1996
DOI: 10.21236/ada311091
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Model of Navy Second-Term Retention,

Abstract: Separation bonus eligibility 6 The Selective Reenlistment Bonus. 8 The civilian unemployment rate. 9 Career variables 9 Personal characteristics.. Fiscal year of decision. Estimation method Results Descriptive statistics • • VSI/SSB eligibility and retention Other variables Estimation results VSI/SSB eligibility Retention Policy questions and marginal effects Appendix A: Selecting the Zone B sample Appendix B: Determining VSI/SSB eligibility Appendix C: Unemployment rates 35 References 37 List of tables 39 Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Moore et al (1996) found that eligibility for the VSI/SSB and higher AFQT scores have a positive effect on the probability of leaving. All else equal, their findings indicated that women are more likely to stay than are men, but married women are more likely to leave than are married men, indicating an interaction of gender with marital status in the effect on retention.…”
Section: Bmentioning
confidence: 91%
See 4 more Smart Citations
“…Moore et al (1996) found that eligibility for the VSI/SSB and higher AFQT scores have a positive effect on the probability of leaving. All else equal, their findings indicated that women are more likely to stay than are men, but married women are more likely to leave than are married men, indicating an interaction of gender with marital status in the effect on retention.…”
Section: Bmentioning
confidence: 91%
“…Some enlisted retention studies deal explicitly with contract extensions, with some treating them as a separate category and others including them in the stayer group, others treating them as a separate category, and still others limiting the sample to those who reenlist or leave. Quester and Adedeji (1991) and Moore et al (1996) use a binary choice, treating enlistees who extended their contract as stayers. In this thesis, extensions could not be distinguished from reenlistments and both groups were considered stayers.…”
Section: B Methodologymentioning
confidence: 99%
See 3 more Smart Citations